Battery module thermal management based on liquid cold plate with heat transfer enhanced fin. (10th May 2019) - Fu, Jiaqi; Xu, Xiaoming; Li, Renzheng
Summary: Battery, as the main energy storage element, directly affects the performance of electric vehicle. Battery thermal management research is required as the battery performance influenced by temperature obviously. This article selects liquid cold plate with different heat transfer enhanced fins as the research object. The angle and length of fins are chosen as the variables. Computational fluid dynamics (CFD) methods and experiments are used in this research. The fin angle of 15°, 30°, and 45° and fin length of 8, 10, 12 mm are selected to compose enhanced fins. The results indicate that heat transfer fins inside liquid cold plate can significantly decrease the highest temperature of battery module and temperature difference among cells. Otherwise, different fin angle and fin length can achieve different heat dissipation performance, which is not positive correlation. Then the design reference of heat transfer enhanced fin in liquid cold plate is offered. Abstract : The angle and length of heat transfer fins are chosen as the variables. CFD method and experiments are used to research them. Heat transfer fins inside liquid cold plate can significantly decrease the highest temperature of battery module and temperature difference among cells. There exists an appropriate fin angle to meet the best requirements of heat dissipation. Both the increase of fin length and fin angle can lead to the increase of pressure loss inside liquid cold plate. Otherwise, the angle of fin influences more.